Identification of Biomarkers for Predicting Ovarian Reserve of Primordial Follicle via Transcriptomic Analysis - Liu, Li; Liu, Biting; Li, Ke; Wang, Chunyan; Xie, Yan; Luo, Ning; Wang, Lian; Sun, Yaoqi; Huang, Wei; Cheng, Zhongping; Liu, Shupeng (Frontiers in Genetics, 2022)
Ovarian reserve (OR) is mainly determined by the number of primordial follicles in the ovary and continuously depleted until ovarian senescence. With the development of assisted reproductive technology such as ovarian tissue cryopreservation and autotransplantation, growing demand has arisen for objective assessment of OR at the histological level. However, no specific biomarkers of OR can be used effectively in clinic nowadays. Herein, bulk RNA-seq datasets of the murine ovary with the biological ovarian age (BOA) dynamic changes and single-cell RNA-seq datasets of follicles at different stages of folliculogenesis were obtained from the GEO database to identify gene signature correlated to the primordial follicle pool. The correlations between gene signature expression and OR were also validated in several comparative OR models. The results showed that genes including Lhx8, Nobox, Sohlh1, Tbpl2, Stk31, and Padi6 were highly correlated to the ovarian reserve of the primordial follicle pool, suggesting that these genes might be used as biomarkers for predicting ovarian reserve at the histological level.